2009
DOI: 10.1002/cssc.200800171
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cellulose Fatty Esters as Plastics—Influence of the Degree of Substitution and the Fatty Chain Length on Mechanical Properties

Abstract: Alternative films: The effect of the chain length and the degree of substitution on the mechanical and hydrophobic properties of various cellulose fatty ester plastic films was studied. The results suggest that the cellulose ester plastic films are promising alternatives to petrochemical commodity plastics such as polyethylene.Cellulose-based plastic films were prepared by acylating cellulose in homogeneous media under microwave irradiation with fatty acyl chlorides containing either saturated or unsaturated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 28 publications
11
83
3
Order By: Relevance
“…Simple and mixed cellulose esters of short-chain carboxylic acids (C2 to C4) are produced in industrial scale to obtain synthetic fibers, photographic and X-ray films, coatings, textile and cigarette filter industries (Crépy et al 2009). Commercial cellulose acetate is typically prepared using acetic acid and acetic anhydride in the presence of a strong acid catalyst (Cheng et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Simple and mixed cellulose esters of short-chain carboxylic acids (C2 to C4) are produced in industrial scale to obtain synthetic fibers, photographic and X-ray films, coatings, textile and cigarette filter industries (Crépy et al 2009). Commercial cellulose acetate is typically prepared using acetic acid and acetic anhydride in the presence of a strong acid catalyst (Cheng et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed to prepare LCCEs. These methods involved heterogeneous acylation by using acyl chloride, acid chlorides under vacuum or aliphatic acids with trifluoroacetic acid [3], and homogeneous acylation in DMAc/LiCl [4][5][6] or in ionic liquids [7,8]. Studies have shown that the maximum degree of substitution (DS) of LCCEs synthesized in ionic liquid system was up to approximately 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…The esterification of cellulose is the oldest polymer modification reaction known and its relevance has never lost its impact. In the last few decades, long chain cellulose esters have still been prepared by grafting fatty acids and their derivatives onto cellulose, either by surface or bulk reactions, employing various methods (Berlioz et al 2009;Boufi and Belgacem 2006;Bras et al 2007;Crepy et al 2009;Freire et al 2006;Pasquini et al 2008;Peydecastaing et al 2006). These cellulose derivatives, which were elaborated with different substrates and purposes, showed an enhanced hydrophobic character with water contact angles some times exceeding 90°.…”
Section: Chemical Modificationsmentioning
confidence: 99%